Computational Modelling Based Recommendation on Optimal Dialysis Needle Positioning and Dialysis Flow in Patients With Arteriovenous Grafts. (February 2020) - Quicken, Sjeng; Huberts, Wouter; Tordoir, Jan; van Loon, Magda; Delhaas, Tammo; Mees, Barend
Abstract : Objective: Arteriovenous grafts (AVGs) typically lose patency within two years of creation due to venous neointimal hyperplasia, which is initiated by disturbed haemodynamics after AVG surgery. Haemodialysis needle flow can further disturb haemodynamics and thus impact AVG longevity. In this computational study it was assessed how dialysis flow and venous needle positioning impacts flow at the graft-vein anastomosis. Furthermore, it was studied how negative effects of dialysis needle flow could be mitigated. Methods: Non-physiological wall shear stress and disturbed blood flow were assessed in an AVG model with and without dialysis needle flow. Needle distance to the venous anastomosis was set to 6.5, 10.0, or 13.5 cm, whereas dialysis needle flow was set to 200, 300 or 400 mL/min. Intraluminal needle tip depth was varied between superficial, central, or deep. The detrimental effects of dialysis needle flow were summarised by a haemodynamic score (HS), ranging from 0 (minimal) to 5 (severe). Results: Dialysis needle flow resulted in increased disturbed flow and/or non-physiological wall shear stress in the venous peri-anastomotic region. Increasing cannulation distance from 6.5 to 13.5 cm reduced the HS by a factor 4.0, whereas a central rather than a deep or superficial needle tip depth reduced the HS by a maximum factor of 1.9. Lowering dialysis flow from 400 to 200 mL/min reduced the HS by a factor 7.4. Conclusion: Haemodialysis needle flow, cannulation location, and needle tip depth considerably increase the amount of disturbed flow and non-physiological wall shear stress in the venous anastomotic region of AVGs. Negative effects of haemodialysis needle flow could be minimised by more upstream cannulation, by lower dialysis flow and by ensuring a central needle tip depth. Since disturbed haemodynamics are associated with neointimal hyperplasia development, optimising dialysis flow and needle positioning during haemodialysis could play an important role in maintaining AVG patency.